A STUDY OF CALCIFICATION OF THE SUPRASPINATUS TENDON - NAKAJIMA, Kiyotaka (Journal of The Showa Medical Association, 1991)
With the advancement of degeneration, tendons decrease markedly in elasticity and become fragile. This is attributed mainly to degeneration of the collagen fiber, but I hypothesize that microscopic calcification of the tendon fiber might be part of the cause of the process by which tendons become fragile. I examined supraspinatus tendons in various age groups under an atomic absorption-flame emission spectrophotometer to determine tissue calcium content. The subjects were 30 cases of supraspinatus tendon, obtained from fresh cadavers and operation, ranging in age from 17 to 90 years. The tissut collected was dried at 105°C for 48 hours, decomposed with nitric acid and perchloric acid and then subjected to atomic absorption analysis to determine its calcium content. A comparative study, using a transmission electron microscope, was also carried out on 6 cases including all age groups. The results are summarized as follows : 1) Aging was proportional to the calcium content in the supraspinatus tendon, with a coefficient of correlation of 0.676. 2) The calcium content of the tendon in patients over 60 years old with rupture of the supraspinatus tendon was significantly higher than that in patients of about the same age with other diseases (p<0.05) . 3) Under the electron microscope, the collagen fiber had a well-defined margin contour in the young. In middle age, the contour of the margin of collagen fiber was as sharp as that in the young, but division of the bundle of fibers was apparent. In the elderly, the contour of the collagen fiber was obscure. Many deposits, considered to be calcium deposits, were seen in various places, and some of the deposits appeared to be massive.